Effect of a structured physical therapy program on pain, disability, and mobility in chronic nonspecific low back pain - Zejnullahi, Hajrie; Aruqi , Lirije; Tahirbegolli, Bernard; Aliu, Mejdi; Qorolli, Merita (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to evaluate the effectiveness of structured physiotherapy program in reducing pain intensity (PI), and in improving functional disability (FD), and functional mobility (FM) in individuals with chronic nonspecific low back pain (CNSLBP). This was a prospective cohort study with an interventional design encompassing 47 outpatients with CNSLBP aged 18-64 (48.0±12.6), comprising 15 males and 38 females. A six-week structured physical therapy program included a two-week (5x/ week) supervised physiotherapy regimen, followed by a four-week home exercise programme (HBE) encompassing stretching, endurance, strengthening and aerobic exercises. PI, FD, and FM were assessed using a numerical rating scale (NRS), the Oswestry Disability Index (ODI), and a 30-second sit-to-stand test (30STS) respectively. NRS scores showed a significant decrease from baseline (5.93±2.95) to six weeks (2.68±1.68) after physiotherapy intervention (p<0.05). ODI scores significantly decreased from 16.36±5.70 to 7.39±5.02 (p<0.05) indicating an improvement in FD. The 30STS test reviled a significant enhancement following the two-week physiotherapy intervention (t=3.225, p=0.002). Our study showed a significant reduction in PI and an improvement in FD and FM after a two-week physiotherapy intervention. In addition, the four-week HBE program contributes to continuous improvement in PI and FD, highlighting its effectiveness in supporting and increasing the profits of the supervised phase.